Vitrectomy with internal limiting membrane peeling for stellate nonhereditary idiopathic foveomacular retinoschisis: a case report (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To report a case of a rare disease, stellate nonhereditary idiopathic foveomacular retinoschisis (SNIFR), its clinical course and the results of vitrectomy with internal limiting membrane (ILM) peeling.Material and Methods: Comprehensive ophthalmological examination (including visual acuity testing, biomicroscopy, ophthalmoscopy, tonometry, Goldmann kinetic perimetry and imaging with ocular ultrasound, optical coherence tomography (OCT), and fluorescein angiography (FA)) was performed before surgery and 1 month, 3 months and 12 months thereafter.Results: The patient had no somatic comorbidity and complained only of a gradual deterioration in vision over two years. She experienced an improvement in vision after vitrectomy with ILM peeling. This treatment contributed to a substantial reduction in retinal thickness and the restoration of macular vitreoretinal interface.Conclusion: This case indicates the efficacy and safety of surgical treatment for SNIFR, because this treatment contributed to the restoration of macular vitreoretinal interface and no recurrence was observed over a 1-year follow-up period.
Keywords: stellate nonhereditary idiopathic foveomacular retinoschisis; vitrectomy; optical coherence tomography; foveomacular retinoschisis; internal limiting membrane